Combination of closing-wedge distal femoral osteotomy and modified tibial plateau levelling osteotomy for the treatment of medial patellar luxation and concomitant cranial cruciate ligament disease in dogs - Costa Junior J.S. (2024)
© 2024Considering the prevalence of cranial cruciate ligament disease (CCLD) and concurrent medial patellar luxation (MPL) among dogs, and the concomitant bone deviations routinely identified, the aim of this study is to evaluate the efficacy of the combination between distal femoral osteotomy (DFO) and modified tibial plateau levelling osteotomy (mTPLO) for the treatment of MPL with distal femoral varus, tibial torsion, and CCLD. Dogs with concurrent MPL and CCLD that underwent DFO and mTPLO procedures were included. Subjective clinical evaluations of gait and pre-operative and immediate post-operative radiographic examinations were performed. Surgical data were documented. The anatomical lateral distal femoral angle (aLDFA), femoral varus angle, mechanical medial proximal tibial angle, and tibial plateau angle (TPA) were compared between the pre- and post-operative periods. A total of 12 dogs were included in this study. Closing-wedge DFO and mTPLO procedures were performed on 14 limbs. The mean pre-operative and post-operative aLDFA values were 104.8 ± 3.9° and 95.4 ± 2.4°, respectively. TPA values were 26.2 ± 3.7° pre-operatively and 6.3 ± 3.2° post-operatively. Bone healing was observed in 7.1 %, 71.3 %, and 85.5 % of patients at the first, second, and third follow-up, respectively. Lameness was resolved in 28.5 %, 78.5 %, and 100 % at 30, 60, and 90 days, respectively. No major peri- or post-operative complications were reported. The combination of mTPLO and DFO aligns the stifle extensor mechanism, promoting dynamic stabilization. It can be considered for the treatment of concurrent MPL and CCLD in dogs, performed as a single procedure, and is associated with favorable short-term outcomes.